2015
DOI: 10.2139/ssrn.2622114
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Taxes from Labor to Consumption: More Employment and More Inequality

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…For example, micro-simulations of a tax shift from the personal income to the value added tax (VAT) confirm the regressive impact of this shift (e.g. Pestel and Sommer, 2013;Decoster et al, 2011). Some studies have found that after accounting for labour-supply adjustments, the adverse distributional impact is smaller due to increased work incentives.…”
mentioning
confidence: 98%
“…For example, micro-simulations of a tax shift from the personal income to the value added tax (VAT) confirm the regressive impact of this shift (e.g. Pestel and Sommer, 2013;Decoster et al, 2011). Some studies have found that after accounting for labour-supply adjustments, the adverse distributional impact is smaller due to increased work incentives.…”
mentioning
confidence: 98%
“…In addition, our results speak to the literature analyzing the distributive effects of tax shifts from labor income toward other tax bases such as consumption (e.g., Pestel and Sommer 2017). So far, little empirical work has been dedicated to property tax related simulations, mostly driven by data limitations.…”
Section: Introductionmentioning
confidence: 52%
“…In order to be able to handle them simultaneously, we imputed VAT and excise tax payments in EU-SILC. Similarly to other studies analysing the redistributive effect of indirect taxes, such as De Agostini et al (2017), Pestel and Sommer (2017) or Savage (2017), we used a regressionbased method for the imputation. We constructed a regression model of VAT payment in the Household Budget Survey based on overlapping socio-demographic variables 6 as explanatory variables and applied this model to predict VAT in EU-SILC.…”
Section: Data and Assumptionsmentioning
confidence: 99%